+0  
 
0
326
1
avatar

como pongo 2 a la menos2

 10 dic. 2014

Mejor Respuesta  

 #1
avatar+79 
+3

$${{\mathtt{2}}}^{-{\mathtt{2}}} = {\frac{{\mathtt{1}}}{{{\mathtt{2}}}^{{\mathtt{2}}}}} = {\frac{{\mathtt{1}}}{{\mathtt{4}}}} = {\mathtt{0.25}}$$

.
 21 dic. 2014
 #1
avatar+79 
+3
Mejor Respuesta

$${{\mathtt{2}}}^{-{\mathtt{2}}} = {\frac{{\mathtt{1}}}{{{\mathtt{2}}}^{{\mathtt{2}}}}} = {\frac{{\mathtt{1}}}{{\mathtt{4}}}} = {\mathtt{0.25}}$$

rubenlosada 21 dic. 2014

57 Usuarios en línea

avatar
avatar
avatar